Corrosion of Mild Steel in Saline Environments: Mechanisms, Influencing Factors, and Recent Mitigation Strategies - Thaqeef Murtada Jawad (Journal of Wasit for Science and Medicine, 2026)
Mild steel is prized because of its mechanical qualities and low prices but very vulnerable to corrosion in salty conditions such as in the marine areas. The paper examines its weight loss, potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) corrosion behavior in 3.5 wt.% NaCl. Findings indicate that the rate of corrosion rises with the chloride concentration to a certain optimum and after that, the rate of oxygen diffusion begins to be limiting. High temperatures and acidic PH promote corrosion and an increase in flow velocity increases the mass transfer and promotes corrosion rates. The splash zone is the worst of all the marine zones. Recent mitigation measures are critically assessed: an environmentally-friendly organic/inorganic hybrid inhibitor has 95.75 % inhibition potential and graphene-based coating has more than 1000 hours of protection in saline conditions. Also, prediction models, based on machine learning, are talked about. The results provide very useful information to the design and maintenance of mild steel structures in coastal and marine works to overcome economic, safety and environmental challenges.